SAFETY AND SECURITY ASSESSMENT OF TOURIST DESTINATIONS: A FIELD STUDY IN A NIGERIAN GEOPARK: Safety and Security Assessment of Tourist Attraction Sites (Journal of Event, Tourism and Hospitality Studies, 2022)
In the travel industry, safety and security are imperative and any attraction sites which ignore these tasks stand to lose out on the intense competition for tourists. One way to ensure that safety and security are satisfactorily provided is to regularly assess and seek the perceptions of stakeholders. Studies that make such an attempt, particularly in a Nigerian Geopark are relatively underrepresented in the literature. This study therefore evaluates safety and security situations at a large geopark and one of the most visited tourist destinations in Nigeria. Through direct observation, an on-site assessment of safety and security measures was undertaken by experts. The assessment instrument was designed using an empirical adaptation of standards which have been suggested in the literature. In addition, members of the site management were interviewed on various outcomes of the field study. Generally, the safety and security architecture in the study area appeared to be insufficient as the management seemed restrained to be too proactive for fear of scaring wildlife and visitors. Besides, the management did not consider the site to be under any serious threat as no major accident and/or crime has been recorded in the last decade. The study concludes that safety and security approaches in the study area do not reflect standard measures but rather cautious approach and an overly dependence on a supposed good past record. The result of this study can facilitate standard practice for safety and security in tourist destinations. This study fills the knowledge gap by providing information on the Nigerian experience regarding safety and security of Geopark in the Global South.